Approaches to the treatment of early rheumatoid arthritis with disease-modifying antirheumatic drugs - Sizova, Lyudmila (Blackwell Science Inc, 2008)
This paper reviews recent approaches to treatment of early rheumatoid arthritis (RA) with disease-modifying antirheumatic drugs (DMARDs). The literature on treatment the early RA published between 1995 and 2007 was accessed through the PubMed database from the National Library of Medicine. Keywords were ‘early rheumatoid arthritis’, ‘disease-modifying antirheumatic drugs’, ‘biologic agents’ and ‘combination therapy’. Only results of trials on human subjects that directly measured the effects of DMARDs or biological agents on clinical, laboratory parameters and radiological progression of early RA were selected. Combination therapy suppresses RA activity and radiological progression more effectively than monotherapy. If better control of RA is evident after 3–6 months of treatment with the combination of DMARDs, one must still decide whether to stop the first DMARD, stop the second, or continue with the combination. Combination therapy biological agents (infliximab, adalimumab) with methotrexate and etanercept therapy alone may induce remission in many patients with early RA. It is a method of choice in patients with an adverse prognosis. The main indications for combination therapy ‘standard’ DMARDs or combination 1 DMARDs with a biological agent are such variables as detection of a shared epitope, increase of concentration of anticyclic citrullinated peptide antibodies, rheumatoid factor, C-reactive protein, 28-joint disease activity score, Sharp score and presence of erosion in joints. The majority of rheumatologists believe that patients with RA should be treated with DMARDs earlier rather than later in the disease process. Further trials should establish the optimal approaches to early RA therapy.